Development and Application of a High-Speed Reacting Flow Solver in OpenFOAM - Adhikari, Sanjeev; Tang, Hao; Bhattrai, Sudip (Journal of Innovations in Engineering Education, 2022)
A numerical study was conducted to verify and validate a new solver, named hyperReactingSodFoam, based on the OpenFOAM toolbox. This study mainly focuses on verification of solver’s computational capability to compute hypersonic flows involving shock-induced combustion, and its applications. This investigation is limited to inviscid flow and incorporates Minmod limiter to achieve total variation diminishing property. Analysis of a practical case was conducted by simulate and validate hypersonic blunt body projectile experiments at Mach 6.46 and 4.18. Likewise, to demonstrate the wider applicability of solver, a standing detonation in an oblique detonation wave engine combustor with a sharp as well as a blunted wedge geometry was studied. It was observed that, for a given flow condition and combustor geometry, a sharp wedge has a better mass-weighted average pressure recovery comparative to the blunted wedge. However, blunted wedge geometry provides a better picture of the detonation phenomenon as a practical wedge will have finite bluntness. In addition, the concept of the detonation induction length becomes less relevant for a blunted wedge.